Potential Analysis Of Street Lighting Tax On Regional Original Income In Tana Toraja Regency - Adnan Musyawir Rayendra Adnan (Pustaka Digital Indonesia, 2021)
The purpose of this study was to determine the potential of PPJ in Tana Toraja Regency, to determine the contribution of PPJ to PAD and PD in Tana Toraja Regency, to determine the effectiveness of PPJ in Tana Toraja Regency and to determine the prospect of PPJ acceptance in Tana Toraja Regency. The types of data used are quantitative data and time series data with a time span of 2014 to 2018. The results of this research are that the potential for PPJ in Tana Toraja has increased, then for PPJ's contribution to PAD and PD has stability for 5 years, for the level of effectiveness of PPJ in Tana Toraja it is quite satisfactory, the prospect of PPJ acceptance in Tana Toraja is already good.